The Relationship Between Hr's Use Of Social Media And The Employer Branding Process - Syamsulbari Syamsulbari; Ali Badarudin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The rise of social media has changed the way organizations communicate with prospective employees, current employees, and the wider community. Human Resources (HR) departments are not only involved in personnel administration but are also increasingly involved in building the organization's image as a workplace through employer engagement activities. Branding on social media. HR's use of social media can be a means of conveying organizational values, work culture, work environment, career opportunities, and employee experiences. Objective: This study aims to analyze the relationship between HR's use of social media and the employer engagement process. branding .This study used a quantitative analytical design with a cross-sectional approach . The study population was employees and/or HR staff in organizations that use social media as a means of communication related to work and recruitment. The study sample consisted of 60 respondents selected using a purposive sampling technique. Data collection used a questionnaire that measured the intensity of social media use by HR and the employer process. branding . Data analysis was conducted univariately and bivariately using the Chi- Square test with a significance level of α = 0.05. Based on simulation data, 38 respondents (63.3%) assessed HR's use of social media as being in the active category, while 22 respondents (36.7%) assessed HR's use of social media as being in the less active category. Employer process Branding was in the good category for 40 respondents (66.7%) and poor for 20 respondents (33.3%). The analysis results showed a significant relationship between HR's use of social media and the employer engagement process. branding (p < 0.05). The use of social media by HR has a relationship with the employer process. Branding . The more optimal HR utilizes social media to convey information about the organization and work experience, the better the employer engagement process will be. branding that is formed.